2017
DOI: 10.1097/nrl.0000000000000110
|View full text |Cite
|
Sign up to set email alerts
|

Ischemic Stroke in Young Adults

Abstract: Etiological diagnosis of stroke in the young is challenging for clinicians. Hence, a more effective classification scheme, better investigative mechanisms, and correct determination of causal associations in ischemic stroke are needed. Thrombophilia screening should be performed in the presence of relevant clinical signs and/or family history.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 10 publications
2
2
0
1
Order By: Relevance
“…The percentage of hypertension was 21% in this study, which was similar to Montanaro et al (25) in Brazil who found about 20% of patients were hypertensive but lower than most of the other studies such as Chraa et al (10) in Morocco, Fahmi et al (26) in Egypt, Schneider et al (23) in Estonia, Magwood et al (22) in US, and Kissela et al (8) where the percentage of hypertensive patients ranged from 36% to 56% of their patients.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…The percentage of hypertension was 21% in this study, which was similar to Montanaro et al (25) in Brazil who found about 20% of patients were hypertensive but lower than most of the other studies such as Chraa et al (10) in Morocco, Fahmi et al (26) in Egypt, Schneider et al (23) in Estonia, Magwood et al (22) in US, and Kissela et al (8) where the percentage of hypertensive patients ranged from 36% to 56% of their patients.…”
Section: Discussionsupporting
confidence: 87%
“…Regarding parenchymal imaging, most of the studied patients (74%) had infarctions in the anterior circulation which was nearly similar to 71% and 80 % of patients found by Lutski et al (30) and Montanaro et al (25) respectively to have anterior circulation strokes. As regards vascular imaging, 70% of the studied patients had normal vascular imaging, about 15% had atherosclerotic vasculopathy [5.7% had extracranial atherosclerosis, 5.6% had intracranial atherosclerosis and 2.8% had combined intracranial and extracranial atherosclerosis] and 15% had non atherosclerotic vasculopathy.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…There has been increasing interest in the rising figures of stroke incidents in working young adults. According to one transversal retrospective study which analyzed electronic medical records (EMR) data during a four-year period for 134 patients aged 18 - 45, the average age of stroke patients appeared to be 33 years, and the majority were females (56%) [ 4 ]. However, the proportion of the first-ever stroke in young adults differed from country to country, ranging from < 5% to 20% of all strokes [ 1 ].…”
Section: Reviewmentioning
confidence: 99%
“…На актуальность проблемы указывает и высокая частота криптогенного инсульта (15-40%), т.е. инсульта неустановленной этиологии [1][2][3][4][5]. Кроме того, за последние годы изменились причины ИИ.…”
unclassified